2003
DOI: 10.1080/17461390300073302
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostics of anaerobic power and capacity

Abstract: Testing procedures for the assessment of anaerobic energy metabolism during muscular work have not yet gained the relevance of tests assessing maximal aerobic power. The diagnosis of aerobic power allows one, through the choice of an adequate testing protocol, to design a test that mainly measures the power of aerobic metabolism by means of indicators like VO 2max and lactate. With regard to tests for the assessment of anaerobic power and capacity, however, alactic, lactic, and oxidative components of energy e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
99
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(114 citation statements)
references
References 21 publications
3
99
0
2
Order By: Relevance
“…Afterward, peak power (sprint PPO) and mean power (sprint MPO) were determined. Capillary samples from the earlobe were collected before and in minute intervals (1′–10′) after the test to determine the “maximal rate of lactate accumulation (dLa/dt max )” according to Heck et al (2003) and Hauser et al (2014a): leftdLa/dtmax false(mmol·L-1·s-1false)=false([La]max-[La]restfalse) false(texerc-talacfalse)-1 where [ La ] max ( mmol · L −1 ) = maximal lactate concentration after the exercise; [ La ] rest ( mmol · L −1 ) = lactate concentration before exercise; t exerc (seconds) = duration of exercise; t alac (seconds) = period at the beginning of exercise for which (fictitiously) no lactate formation is assumed. The t alac for each subject was set as the time to sprint PPO (seconds).…”
Section: Methodsmentioning
confidence: 99%
“…Afterward, peak power (sprint PPO) and mean power (sprint MPO) were determined. Capillary samples from the earlobe were collected before and in minute intervals (1′–10′) after the test to determine the “maximal rate of lactate accumulation (dLa/dt max )” according to Heck et al (2003) and Hauser et al (2014a): leftdLa/dtmax false(mmol·L-1·s-1false)=false([La]max-[La]restfalse) false(texerc-talacfalse)-1 where [ La ] max ( mmol · L −1 ) = maximal lactate concentration after the exercise; [ La ] rest ( mmol · L −1 ) = lactate concentration before exercise; t exerc (seconds) = duration of exercise; t alac (seconds) = period at the beginning of exercise for which (fictitiously) no lactate formation is assumed. The t alac for each subject was set as the time to sprint PPO (seconds).…”
Section: Methodsmentioning
confidence: 99%
“…2 It was assumed that the maximal rates (or power) of aerobic and anaerobic metabolism define LT and thus %VO 2 max by a system of differential equations. [3][4][5][6][7] These differential equations are based on two essential parameters:VO 2 max, as a measure of aerobic power, and the maximal rate of lactate accumulation (VLa max ), as a measure of anaerobic (lactic) power.VLa max is determined by using an all-out (sprint) exercise of 10-15 s and post-exercise lactate kinetics. 5,6V La max is calculated as the difference (La ) between maximal post-exercise lactate concentration (La max ) and resting lactate concentration (La Pre ) that was divided by the difference between test time (t test ) and the period at the beginning of exercise for which no lactate formation is assumed (t alac ) Eq.…”
Section: Introductionmentioning
confidence: 99%
“…The determination of trueV˙normalO2max is a valid test procedure and well established in performance and clinical diagnostics [23]. However, Mader and Heck [3], Bleicher et al [12], Heck and Schulz [14] and Mader [11] showed that on a theoretical basis, trueV˙normalLamax must have a significant influence on PMLSS. In the present investigation trueV˙normalLamax shows no correlation with PMLSS E , which was probably caused by the small range of trueV˙normalLamax values measured in this investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the missing correlation between trueV˙normalLamax and PMLSS E as well as the overestimation of PMLSS C may have been caused by the methodological procedure in determining the maximal anaerobic performance. For example, in the present study trueV˙normalLamax was measured by a sprint-test lasting 15 s. It is possible that testing trueV˙normalLamax by using a test duration lower than 15 s would lead to higher maximal glycolytic rates and therefore on the basis of the same trueV˙normalO2max to a lower PMLSS [3,12,14]. Hauser [24] showed, that trueV˙normalLamax increases by 8% when measured using a 13 s sprint-test compared to a 15 s sprint-test.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation